The effect of Nifedipine on embryo transfer outcomes: A randomized clinical trial - Masoomeh Nataj Majd; Ashraf Moini; Saghar Samimi Sadeh; Ehsan Bastanhagh (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Endometrial receptivity is crucial for embryo implantation, and excessive uterine contraction reduces success. Nifedipine which is a calcium channel blocker, could decrease uterine contraction and improve pregnancy outcomes. Objective: This study aimed to assess the effect of Nifedipine before embryo transfer on the pregnancy outcome in women undergoing in vitro fertilization (IVF) in a tertiary center in Iran. Materials and Methods: 150 women who were candidates for IVF were randomly assigned into 2 groups: group 1 received 20 mg Nifedipine 30 min before embryo transfer, and group 2 received no intervention. Blood pressure of the participants was monitored every 10 min for 1 hr under the supervision of an anesthesiologist. Finally, implantation rate and chemical and clinical pregnancy rates were compared between groups. Results: At the end of the study, 140 participants were included in the final analyses. No significant difference was observed in clinical pregnancy rates between groups (20% vs. 22%, p = 0.51) Conclusion: Nifedipine administration before embryo transfer does not improve the implantation and clinical pregnancy rates in women undergoing IVF.